Studi Meta-analisis: Welas Diri dan Kecemasan - Clarissa Firanda Polii; Ananta Yudiarso (Jurnal Psikologi Integratif, 2023)
Anxiety is defined as a physiological response to the possibility of problems arising in individuals. Anxiety is known to have a relationship with other variables, one of which is self-compassion. Individual self-compassion will be able to influence the level of anxiety. Individuals who have self-compassion will tend to avoid negative emotions that cause anxiety. This meta-analytic study aims to look at the relationship between anxiety and self-compassion in the last five years of research from 2018 to 2023 with a total of 10,489 respondents. The results of the study found that self-compassion had a moderate effect size (-0.55) with heterogeneity (I 2 ) of more than 88.81%, so this study used a random effects size. Therefore, self-compassion is interpreted as having a moderate effect that is negatively correlated with levels of anxiety. Kecemasan didefinisikan sebagai respon secara fisiologis dari kemungkinan munculnya permasalahan pada individu. Kecemasan diketahui memiliki kaitan dengan variabel lain salah satunya welas diri. Welas diri yang dimiliki individu akan mampu mempengaruhi tingkat kecemasan. Individu yang memiliki welas diri akan cenderung terhindar dari emosi negatif yang menyebabkan kecemasan. Studi meta-analisis ini bertujuan untuk melihat hubungan antara kecemasan dan welas diri dalam penelitian lima tahun terakhir dari tahun 2018 hingga 2023 dengan total responden sebanyak 10.489 orang. Hasil penelitian menemukan bahwa welas diri memiliki medium effect size (-0,55) dengan heterogenitas (I 2 ) lebih dari 88,81%, sehingga penelitian ini menggunakan random effects size. Oleh karena itu, welas diri diartikan memiliki efek sedang yang berkorelasi secara negatif pada tingkat kecemasan.